2015
DOI: 10.4314/ajtcam.v12i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of nano-silver particles from leaf and stem extracts of <i>Iboza</i> (<i>Tetradenia riparia</i>)

Abstract: Background: Secondary metabolites derived from plant extracts can be used in the reduction of metal salts into their respective nanoparticles using simple, environmentally friendly and cost effective green synthesis techniques. Metal nanoparticles have important applications in medicine and agriculture. The leaves of Tetradenia riparia (Iboza), an important medicinal species in South Africa, are reported to contain various terpenoids and pyrones which can be used in the reduction of silver nitrate (AgNO 3 ) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…A survey of the literature shows an increasing move towards the green synthesis of NPs using plant extracts [15][16][17][18][19]. We too have reported NP synthesis and characterisation in T. riparia [20,21], a plant used as traditional medicine in South Africa [22,23]. Importantly, Shaik et al [20,21] showed that methanol and aqueous derived NPs displayed similar FTIR spectra.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…A survey of the literature shows an increasing move towards the green synthesis of NPs using plant extracts [15][16][17][18][19]. We too have reported NP synthesis and characterisation in T. riparia [20,21], a plant used as traditional medicine in South Africa [22,23]. Importantly, Shaik et al [20,21] showed that methanol and aqueous derived NPs displayed similar FTIR spectra.…”
Section: Introductionmentioning
confidence: 86%
“…In the latter study, nanoplates (40 nm diameter) were found to be more toxic than nanoparticles (57 nm diameter), based on the decrease in growth and photosynthetic activities. The average diameter of the spherically shaped NPs synthesized from leaf extracts of T. riparia was 26 nm [20,21], hence, according to the literature, they are likely to be highly bio-active.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…), alkaloids, polyphenols, terpenoids, sugars, and many other biologically active phytocompounds are able to reduce metal ions very quickly [ 183 ]. The obtained metallic nanoparticles are then purified by centrifugation and the recovered pellet is dried in the oven [ 184 ].…”
Section: Green Synthesized Plant-based Metallic Nanoparticles As a Mo...mentioning
confidence: 99%